2020
DOI: 10.5114/pjp.2020.95416
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of PON1 L55M, Q192R and I102V polymorphisms and their association with prostate cancer risk in Polish men

Abstract: We tested the association between PON1 L55M, Q192R and I102V polymorphic variants and PC risk in Polish men. DNA from 110 consecutive, newly diagnosed patients hospitalized because of PC and DNA from 110 men -volunteers, healthy at the time of the study. PCR-RFLP method. In our study the average age at PC diagnosis of 55MM genotype carriers from families fulfilling Hereditary Prostate Criteria (HPC) was statistically significantly lower (by 7 years) than the average age at the disease diagnosis of 55MM carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Serum paraoxonase and arylesterase 1 ( PON1 ), also known as A-esterase, is an enzyme encoded by the PON1 gene, which is involved in the process of preventing damage caused by systemic oxidative stress [ 57 ]. Given increasing evidence of its involvement in the development of various cancers, Heise et al [ 58 ] conducted a study focused on PCa but did not find any specific genotype correlated with an increased risk of PCa. However, PON1 remains a gene of interest, and further trials are needed to elucidate a potential connection with PCa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum paraoxonase and arylesterase 1 ( PON1 ), also known as A-esterase, is an enzyme encoded by the PON1 gene, which is involved in the process of preventing damage caused by systemic oxidative stress [ 57 ]. Given increasing evidence of its involvement in the development of various cancers, Heise et al [ 58 ] conducted a study focused on PCa but did not find any specific genotype correlated with an increased risk of PCa. However, PON1 remains a gene of interest, and further trials are needed to elucidate a potential connection with PCa.…”
Section: Resultsmentioning
confidence: 99%
“…No correlation found with PCa Mersch et al [35] BRCA1/2 BRCA2 is associated with ↑ age-specific risk for PCa Silvestri et al [36] BRCA 1/2 BRCA2 is associated with ↑ risk for PCa and aggressive forms Pakkanen et al [25] Hereditary vs. SPCa Earlier disease onset and higher PSA in patients with FH Heise et al [58] PON1…”
Section: Evidence Synthesismentioning
confidence: 99%
“…They found that there was no association between the genotypes of the PON1 polymorphisms and the risk of PC. Also they tried to study the association between the haplotypes of the PON1 polymorphisms and PC risk [1]. However, they used genotype combinations instead of haplotypes.…”
mentioning
confidence: 99%
“…6 Standard, Dynacom Co, Ltd. Kanagawa, Japan). I used raw data which presented in second table of Heise's and her colleagues article [1]. Analysis revealed that the L55M and Q192R polymorphisms in both control (D' = 0.9191, r 2 = 0.1694, c 2 = 35.11, P = 3.1 × 10 -9 ) and prostate cancer (D' = 0.7613, r 2 = 0.1305, c 2 = 29.38, P = 5.9 × 10 -8 ) groups are in tight LD.…”
mentioning
confidence: 99%